Relationship between early nutrition and deep gray matter and lateral ventricular volumes of preterm infants at term-equivalent age - Toppe, Felicia Mareen; Rasche, Tobias; Weiß, Christel; Schock, Alexandra; Felderhoff-Müser, Ursula; Müller, Hanna (World journal of pediatrics, 2023)
Background: The survival of preterm infants has improved over the last decade, but impaired brain development leading to poor neurological outcomes is still a major comorbidity associated with prematurity. The aim of this study was to evaluate the effect of nutrition on neurodevelopment in preterm infants and identify markers for improved outcomes. Methods Totally 67 premature infants with a gestational age of 24–34 weeks and a birth weight of 450–2085 g were included. Clinical parameters and documented diet were collected from medical records. The nutritional analysis comprised the protein, fat, carbohydrate, and energy intake during different time spans. Brain development was assessed by determining deep gray matter (DGM; basal ganglia and thalamus) and lateral ventricular (LV) volumes as measured on cerebral magnetic resonance imaging scans obtained at term-equivalent age (TEA), and potential associations between nutrition and brain volumetrics were detected by regression analysis. Results We observed a negative correlation between mean daily protein intake in the third postnatal week and MRI-measured DGM volume at TEA (P = 0.007). In contrast, head circumference at a corrected age of 35 weeks gestation (P < 0.001) and mean daily fat intake in the fourth postnatal week (P = 0.004) were positively correlated with DGM volume. Moreover, mean daily carbohydrate intake in the first postnatal week (P = 0.010) and intraventricular hemorrhage (P = 0.003) were revealed as independent predictors of LV volume. Conclusion The study emphasizes the importance of nutrition for brain development following preterm birth.
Gesehen am 22.05.2023